2015
DOI: 10.1002/jcb.25420
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Actinomycin‐D Induces Redistribution of Wild‐Type and Mutated Nucleophosmin Followed by Cell Death in Leukemic Cells

Abstract: Specific mutations involving C-terminal part of the nucleolar protein nucleophosmin (NPM) are associated with better outcome of acute myeloid leukemia (AML) therapy, possibly due to aberrant cytoplasmic NPM localization facilitating induction of anti-NPM immune response. Actinomycin D (actD) is known to induce nucleolar stress leading to redistribution of many nucleolar proteins, including NPM. We analyzed the distribution of both wild-type and mutated NPM (NPMmut) in human cell lines, before and after low-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
0
27
1
Order By: Relevance
“…Balusu et al [25] demonstrated that AML cells expressing mutated NPM are more sensitive to disruptive effects of the inhibitor NSC348884 on NPM oligomerization, in comparison with AML cells expressing NPMwt. Recently, we revealed that the localization of NPMmutA is not exclusively cytoplasmic and that a substantial fraction of NPMmutA still resides in the nucleoli [26]. Moreover, we and other authors [26,27] have shown that due to heterooligomer formation, subcellular distribution of NPMmutA changes when the cells are co-transfected with NPMwt.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Balusu et al [25] demonstrated that AML cells expressing mutated NPM are more sensitive to disruptive effects of the inhibitor NSC348884 on NPM oligomerization, in comparison with AML cells expressing NPMwt. Recently, we revealed that the localization of NPMmutA is not exclusively cytoplasmic and that a substantial fraction of NPMmutA still resides in the nucleoli [26]. Moreover, we and other authors [26,27] have shown that due to heterooligomer formation, subcellular distribution of NPMmutA changes when the cells are co-transfected with NPMwt.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, we revealed that the localization of NPMmutA is not exclusively cytoplasmic and that a substantial fraction of NPMmutA still resides in the nucleoli [26]. Moreover, we and other authors [26,27] have shown that due to heterooligomer formation, subcellular distribution of NPMmutA changes when the cells are co-transfected with NPMwt. In the present work, we used HEK-293T cell system allowing high amplification of transfected plasmids to investigate the localization of various mutation types.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, it prevents neither Act D-induced nucleolar stress nor activation of the p53-dependent and independent pathways leading cells to death by apoptosis or necrosis, respectively. Since NPM status is not so important in the case of leukemias, AML patients with NPMmut may be expected to have a better outcome of therapy, which is associated with cellular localization of NPMmut (Brodská et al 2016). It is worth noting that Act D in combination with inhibitors of histone deacetylase significantly enhances therapeutic effects (Brodská et al 2016), whereas combined with other standard chemotherapeutic agents little contributes to therapeutic efficiency of these agents (Parsons-Doherty et al 2014).…”
Section: Nucleolus-mediated Anticancer Strategiesmentioning
confidence: 99%
“…Since NPM status is not so important in the case of leukemias, AML patients with NPMmut may be expected to have a better outcome of therapy, which is associated with cellular localization of NPMmut (Brodská et al 2016). It is worth noting that Act D in combination with inhibitors of histone deacetylase significantly enhances therapeutic effects (Brodská et al 2016), whereas combined with other standard chemotherapeutic agents little contributes to therapeutic efficiency of these agents (Parsons-Doherty et al 2014). However, although Act D is often successful in treatment of a variety of cancers and it is relatively well tolerated, treatment with Act D is restricted mainly by its toxicity at higher doses, but its application at lower doses in combination with other drugs to synergize therapeutic efficacy allows to minimize its genotoxicity toward normal tissues (Choong et al 2009).…”
Section: Nucleolus-mediated Anticancer Strategiesmentioning
confidence: 99%